KONTROVERSI HERMENEUTIKA SEBAGAI MANHAJ TAFSIR - Argo Victoria; Abdullah Kelib (Jurnal Hukum Khaira Ummah, 2017)
The application of hermeneutics as a method of interpretation was still debatable among Muslim scholars. Some of them accepted the presence of hermeneutics as one of the relevant methods to understand the interpretation of al-Qur’an, even though this method came from outside the treasures of Islamic world. Hermeneutics was needed to understand the alQur’an, especially to address contemporary issues which mostly laid no settlement in the classical interpretations. Others to be a priori and utterly rejected the use of hermeneutics as a methodology of interpretation for various reasons. The main reason put forward this group was because this method emerged in the West and was used to understand the bible which some extents provided different characteristics from the interpretation of al-Qur’an. This study brought out controversies of hermeneutics surrounding the reasons of Muslim scholars in which certain group put on descriptive-analytic and looked for compromises on such differences. Therefore, a wise outlook on approaching various disciplines that enter and thrive the discourse of Islamic scholarship which is especially used to understand the alQur’an as a book of guidance should be wisely approached to enrich the scientific insights of Muslims in general.Keywords: Hermeneutics, Controversy, Compromise, Manhaj, Commentary